The Taxation of Capital Gains in Double Tax Convention Models - Soler Roch, María Teresa (2014)
The article deals with the taxation of capital gains in cross-border situations, according to the relevant provision in the different Model Conventions (OECD, UN, and US). Following an introduction to the topic, the article analyzes the concept of capital gains, as well as the allocation rules applicable to gains derived from the alienation of different type of assets, including specific anti-abuse provisions and a final reference to the exit taxes.